Integrating React Strategy and Digital Media Literacy to Improve Speaking Proficiency of Elementary Students - Madani, Madani; Maisarah, Ira; Harahap, Alamsyah (English Education : English Journal for Teaching and Learning, 2023)
The aim of this research is to find out how does Integrating react strategy and digital media literacy improve the students‟ speaking proficiency in Baitul Izzah Elementary School Kota Bengkulu. This research applied Classroom Action Research (CAR) method. The respondents were the fourth grade students Baitul Izzah Elementary School of Kota Bengkulu in academic year 2022/2023 that consisted of 28 students. The result showed that integrating react strategy and digital media literacy can improve the students‟ speaking proficiency in term of accuracy in vocabulary. The improvement was showed by the students‟ average score in term of vocabulary in  cycle 1 test (73,89) that included into “satisfactory” category; and average score in cycle II test was (83,46) that included into “very good” category. It means that the students got 12.95% of improvement after getting actions for two cycles.